For analysis of essays: methodological proposal - Núñez Moya, Jairol (2017)
The article proposes the main theoretical approaches and characteristics of the essay to rescue the main determinant that their writing shows: the relationship with social reality. This fundamental aspect leads to revise some useful resources for analysis in an effort to continue the form-content relationship. Thus, the production of rhetorical fact, the structure of writing and essayist strategies are articulated ideologically so that its presence in the text allows the critic recognize through the semiotic and discursive exercise, themes and categories open to interpretation. From these elements a proposed methodological that goes since the description to interpretation and explanation in order to standardize a procedure that may be useful to deepen the social function that is characteristic is performed.